Preiser disease in pediatric population – a review - Kopcik, Katarzyna; Kwinta, Robert (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Preiser disease is an avascular necrosis of the scaphoid. It is a rare disease, and even less common among the pediatric population. Disease is idiopathic, occurring without trauma or scaphoid non-union. Diagnostic methods include classic radiology, CT, MRI and bone scan. Treatment may be both surgical and conservative, and main aim is pain relief and widening range of motion of the wrist. The main aim of this paper is to summarize available knowledge about Preiser disease in the pediatric population. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The paper is based on scientific publications available in PubMed and NCBI databases. After evaluation of abstracts, papers were selected and analyzed, considering the references citied. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. Preiser disease is rare in the pediatric population. Children tend to present better results after conservative treatment than adults. Currently there are no unified treatment recommendations in Preiser disease, as knowledge about this condition is still limited. Wider research is vital to unify management recommendations. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Preiser disease can affect patients of both sexes at any age, but it is exceedingly rare in children. There is a need for controlled randomized studies to establish the treatment standards, which is challenging due to the rarity of the disease. By now, non-surgical treatment tends to be the most common among the pediatric population. Surgical methods implemented in this condition include vascularized bone grafts and proximal row carpectomy.